The Challenges of Conducting Qualitative Research on "couples" in Abusive Intimate Partner Relationships Involving Substance Use. (March 2021) - Love, Beverly; Henderson, Juliet; Johnson, Amy; Stephens-Lewis, Danielle; Gadd, David; Radcliffe, Polly; Gilchrist, Elizabeth; Gilchrist, Gail
Undertaking qualitative dyad or couple interviews involving intimate partner abuse and substance use presents considerable ethical, safeguarding, and theoretical challenges throughout the research process from recruitment to conducting interviews and analysis. These challenges and how they were managed are outlined using the experience from a qualitative study of 14 heterosexual "couples" that explored the complex interplay between intimate partner abuse and substance use. Managing these challenges for participants, their families, and researchers included the use of safeguarding protocols and procedures to manage risk and the provision of clinical support for experienced researchers. Researchers often felt drawn into the conflicts and complex dynamics of opposing accounts from the male and females' relationship which could be emotionally and methodologically taxing. Researchers discussing their analysis and felt experiences with each other provided a reflexive space to manage emotions and stay close to the theoretical underpinnings.